The Nexus between Macro-Prudential Banking Regulation, Interest Rate Spread and Monetary Policy in South Africa - Batsirai, Shayanewako Varaidzo; Tsegaye, Asrat; Khamfula, Yohane (Journal of Economics and Behavioral Studies, 2019)
This study is an empirical attempt to investigate the nexus between macro-prudential banking regulation, interest rate spread and monetary policy in South Africa. The effectiveness of monetary policy and alarmingly wide interest rate spread has been a contentious issue in the corridors of central banks across the globe in this lifetime. This has been largely because monetary policy alone proved to be less efficient in mitigating the effects of systemic risk, particularly during the 2007 financial crisis, necessitating the need for macro-prudential banking regulation. Time series dataset spanning from 1994Q1 to 2016Q4 is employed to carry out this study using the restricted Vector Autoregressive (VAR) model, that is, the Vector Error Correctional Model (VECM). The results show that there is no long-run causality running from trade openness, real exchange rate financial depth interest rate spread and credit growth to the repo rate in South Africa. A short run causality running from credit growth to the repo rate exists from the estimated model. In addition, the empirical results exhibited evidence that interest rate spread has a dampening effect on monetary policy but in the long-run this effect seems reversible in South Africa. Therefore, in order to ensure financial stability, care has to be taken by the South African Reserve Bank and government in choosing the best tool-kit of macro-prudential banking regulation as it can be used to disguise the symptoms of a lax monetary policy framework.